Using Arabic Picture Story Media Enhance Religius Character Student in Primary School - Fajriyah, Ayu Rohmatul; Fahyuni, Eni Fariyatul (MUADDIB Jurnal Kependidikan dan Keislaman, 2024)
This research includes the type of research development that aims to produce products using the Dick and Carey model. The   product   of   Arabic  pictorial   story   media   enhance religious  students  at  SD  Muhammadiyah  I,  Lab  school Umsida.   Data   analysis   in   the   form   of   qualitative and quantitative descriptive questionnaires from technology experts  and  subject  matter  experts,  as  well  as  comments from students for revision. The arabic pictorial story media enhance religious students were carried out in the form of pre-test and post-test on 32 students with several moral subjects. The pre-test post-test results showed the Sig (2- tailed) value was 0,000 0.05, which means that there were differences in learning outcomes between before and then using Arabic pictorial story media. The results of Arabic pictorial story media enhance religious students effective improving has a support level of 89.94% for increasing the involvement religious characters in school.